Of Hype and Hyperbolas: Introducing the New Economic Geography. - Neary, J (2001)
Reviewing The Spatial Economy by Fujita, Krugman, and Venables, this paper argues that the key contribution of the new economic geography is a framework in which standard building blocks of mainstream economics (especially rational decision making and simple general equilibrium models) are used to model the trade-off between dispersal and agglomeration. The approach thus gives a choice-theoretic basis for a "propensity to agglomerate."